2021
DOI: 10.1136/bmjopen-2020-045835
|View full text |Cite
|
Sign up to set email alerts
|

Improving professional health literacy in hospitals: study protocol of a participatory codesign and implementation study

Abstract: IntroductionIn connection with a hospital stay, patients have to make important health-related decisions. They need to find, understand, assess and apply health-related information, and therefore, require health literacy. Adequately responding to the needs of patients requires promoting the communication skills of healthcare professionals within healthcare organisations. Health-literate healthcare organisations can provide an environment strengthening professionals’ and patients’ health literacy. When developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Data were collected within the PIKoG study ‘As made for us—Improving professional health literacy in hospitals’ [ 56 ]. The study aims at co-designing, implementing, and evaluating a communication concept for clinical departments of a hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected within the PIKoG study ‘As made for us—Improving professional health literacy in hospitals’ [ 56 ]. The study aims at co-designing, implementing, and evaluating a communication concept for clinical departments of a hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the included studies showed, in all cases, that training leads to a broader understanding of HL as a concept in therapeutic professionals. Especially the identification of HL needs, the use of less jargon, raising self-efficacy, and the awareness of adaptations in patient interaction were influenced (Attard et al, 2021;Bird et al, 2022;Finlay et al, 2019;Kaper et al, 2018;Kaper et al, 2019;Koenig & Provident, 2019;Lubasch et al, 2021;Miller-Scott, 2014;Muscat et al, 2021;Toibin et al, 2017). Educational programs should feature general information about HL, techniques to modify therapy for patients with low HL, and giving practical examples (Brown, 2016).…”
Section: Hl Education and Trainingmentioning
confidence: 99%